Subdesenvolvimento e planejamento democrático no pensamento de Celso Furtado - Rafael Pacheco Mourão (2014)
This paper aims to examine the relationship between underdevelopment and democratic planning in the thought of Celso Furtado. Therefore, we rebuilt the controversies surrounding the concept of underdevelopment, exposing the limits and shortcomings as well as the advances that have provided the critical and controversial concept of underdevelopment and hence the key development-underdevelopment and concluded that this concept remains crucial to understanding Brazil. From the perspective of Celso Furtados framework that understands that overcoming underdevelopment involves the adoption of public planning, we conducted an analytical reconstitution in a historical perspective of government planning in Brazil, in order to understand the reasons that limited the practice of public planning. Finally, we present the controversy surrounding the proposed "democratic planning" of Celso Furtado, considering the criticisms of this formulation in order to reaffirm the validity of the proposed "democratic planning" as a more Republican path to the exercise of public planning and the construction of a development that will lead to a major transformation, and thus making possible the overcoming of underdevelopment in the context of Brazil.